Utilization of wastes of wood is with receipt of heat - Andrashek , Josyp; Krechun, Oleg (Forestry, Forest, Paper and Woodworking Industry, 2007)
Classification and analysis of different power complexes is done for utilization of woodwastes with the purpose of receipt of heat. Practical recommendations are offered from the choice of this equipment of different firms for enterprises with different wastes and power of production